The Impact of the First Year of the COVID-19 Pandemic on Canine Rabies Control Efforts: A Mixed-Methods Study of Observations About the Present and Lessons for the Future - Nadal, Deborah; Abela-Ridder, Bernadette; Beeching, Sarah; Cleaveland, Sarah; Cronin, Katy; Steenson, Rachel; Hampson, Katie (Frontiers in Tropical Diseases, 2022)
Achieving zero human deaths from dog-mediated rabies has been set as a global target for 2030. However, the COVID-19 pandemic has disrupted essential health services across the world, with disproportionate impacts on Neglected Tropical Diseases. Through a mixed-method study using stakeholder questionnaires and in-depth interviews, we examined the scale and nature of disruption from the first year of the pandemic to rabies control programs, and reflected on lessons for the future. Study participants included practitioners and policymakers working in government, academia, international organizations, and the pharmaceutical industry across 48 countries, mainly in Africa and Asia. Mass dog vaccination, essential to rabies control, was most heavily impacted and in 2020, was carried out as planned in just 5% of surveyed countries. Access to post-exposure prophylaxis (PEP) also decreased due to fear of COVID-19 infection and difficulties in reaching health care centers. Dog vaccination and PEP delivery suffered from disruptions to importation and distribution of vaccines. School closures affected rabies awareness activities and, when public events moved online, they could not reach the most disadvantaged groups. Surveillance, already weak, was severely disrupted by movement restrictions which, together with reduced demand for PEP, exacerbated under-reporting. Participants reported growing complaints around free-roaming dogs, with numbers likely to have increased in some settings. In some countries, dog rabies outbreaks and human rabies cases were already ascribed to the pandemic, but further impacts are likely still to be realized. Meanwhile, decreased demand for PEP from COVID-19 constraints could lead to reduced procurement in future. In the wake of post-COVID-19 demands on health services, there is an opportunity for veterinary services to show leadership in progressing the Zero by 30 agenda, particularly in scaling up mass dog vaccination within and across countries, as well as potential to make better use of community-based vaccinators. Countries must further secure stable procurement of dog and human vaccines, classifying them as essential goods prioritized for import and where needed, through sharing of stocks. Dedicated telemedicine services also show promise, for example through fostering participatory disease surveillance, including Integrated Bite Case Management, and delivering up-to-date instructions on the closest sources of PEP.